Ideology and the constitution : essays on constitutional jurisprudence - Coomaraswamy, Radhika; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 1996)
With reference to Sri Lanka; covers the period 1987 to 1993.
Includes bibliographical references.
Keywords: Constitutional law -- Sri Lanka; Constitutional law; Sri Lanka -- Politics and government -- 1978-